2013
DOI: 10.1128/jb.02081-12
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Lipid Biosynthesis, Sliding Motility, and Biofilm Formation by a Membrane-Anchored Nucleoid-Associated Protein of Mycobacterium tuberculosis

Abstract: bBacteria use a number of small basic proteins for organization and compaction of their genomes. By their interaction with DNA, these nucleoid-associated proteins (NAPs) also influence gene expression. Rv3852, a NAP of Mycobacterium tuberculosis, is conserved among the pathogenic and slow-growing species of mycobacteria. Here, we show that the protein predominantly localizes in the cell membrane and that the carboxy-terminal region with the propensity to form a transmembrane helix is necessary for its membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 56 publications
1
37
2
Order By: Relevance
“…Overall, our experimental results rule out a role for Rv3852 as a global transcriptional regulator. The discrepancy between our findings and those of Ghosh et al (21) could be ascribed to the ectopic expression of M. tuberculosis H-NS in M. smegmatis, a species that has no ortholog of rv3852 in its genome (17). The expression system employed by Ghosh and coworkers may have altered the regulatory network in the bacterium, thus generating an aberrant phenotype.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Overall, our experimental results rule out a role for Rv3852 as a global transcriptional regulator. The discrepancy between our findings and those of Ghosh et al (21) could be ascribed to the ectopic expression of M. tuberculosis H-NS in M. smegmatis, a species that has no ortholog of rv3852 in its genome (17). The expression system employed by Ghosh and coworkers may have altered the regulatory network in the bacterium, thus generating an aberrant phenotype.…”
Section: Discussioncontrasting
confidence: 56%
“…3), contrary to the findings of Ghosh and colleagues upon overexpression of M. tuberculosis H-NS in M. smegmatis (21). Moreover, unlike Ghosh et al (21), who reported deregulation of the fatty acid biosynthetic genes kasA and kasB and of the major chaperone gene groEL1, we observed no change in expression of these genes when comparing the global transcriptome of the wild-type strain H37Rv to that of the Δrv3852 mutant by RNA-seq. Besides, we found only two genes involved in fatty acid metabolism (fadD11 and lipQ) and three coding for probable transcriptional regulators (rv0232, mce1R, and rv2989) that were slightly deregulated in expression.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations